Gender, age at onset, and duration of being ill as predictors for the long-term course and outcome of schizophrenia: an international multicenter study. (9th December 2022) - Fountoulakis, Konstantinos N.; Dragioti, Elena; Theofilidis, Antonis T.; Wiklund, Tobias; Atmatzidis, Xenofon; Nimatoudis, Ioannis; Thys, Erik; Wampers, Martien; Hranov, Luchezar; Hristova, Trayana; Aptalidis, Daniil; Milev, Roumen; et al.
Abstract: Background: The aim of the current study was to explore the effect of gender, age at onset, and duration on the long-term course of schizophrenia. Methods: Twenty-nine centers from 25 countries representing all continents participated in the study that included 2358 patients aged 37.21 ± 11.87 years with a DSM-IV or DSM-5 diagnosis of schizophrenia; the Positive and Negative Syndrome Scale as well as relevant clinicodemographic data were gathered. Analysis of variance and analysis of covariance were used, and the methodology corrected for the presence of potentially confounding effects. Results: There was a 3-year later age at onset for females ( P < .001) and lower rates of negative symptoms ( P < .01) and higher depression/anxiety measures ( P < .05) at some stages. The age at onset manifested a distribution with a single peak for both genders with a tendency of patients with younger onset having slower advancement through illness stages ( P = .001). No significant effects were found concerning duration of illness. Discussion: Our results confirmed a later onset and a possibly more benign course and outcome in females. Age at onset manifested a single peak in both genders, and surprisingly, earlier onset was related to a slower progression of the illness. No effect of duration has been detected. These results are partially in accord with the literature, but they also differ as a consequence of the different starting point of our methodology (a novel staging model), which in our opinion precluded the impact of confounding effects. Future research should focus on the therapeutic policy and implications of these results in more representative samples.